Polymorphic lymphoproliferative disorders in patients with rheumatoid arthritis are associated with a better clinical outcome. Issue 4 (4th July 2018) - Tsukui, Daisuke; Kanda, Hiroko; Shinozaki-Ushiku, Aya; Tateishi, Shoko; Takeshima, Yusuke; Nagafuchi, Yasuo; Sasaki, Oh; Iwasaki, Yukiko; Harada, Hiroaki; Shibuya, Mihoko; Sumitomo, Shuji; Shoda, Hirofumi; et al.
Abstract: Objectives: The characteristics of lymphoproliferative disorders (LPD) in patients with rheumatoid arthritis (RA) remain unclear. Therefore, we retrospectively analyzed the clinical characteristics of these patients in our department. Methods: Twenty RA patients who developed LPD between April 2003 and August 2016 in our department were analyzed. Results: All of the RA patients who developed LPD had been treated with methotrexate (MTX). The median weekly and total dosages of MTX were 6.8 mg/week and 2530 mg, respectively. The median duration of MTX administration was eight years. Nineteen patients (95%) achieved complete remission (CR) and 15 (75%) achieved CR with MTX cessation alone. Based on the pathological findings, we divided MTX-associated LPD patients into two groups ( n  = 16); polymorphic LPD (31%) and other groups. CR with MTX cessation alone was achieved in 5 (100%) and 6 (54.5%) patients in the polymorphic LPD and other groups, respectively ( p  = .12). Moreover, the duration from the cessation of MTX to CR was significantly shorter in the polymorphic LPD group than in the other group (5.3 months vs 12.6 months, p  = .01, respectively). Conclusion: Polymorphic LPD, which was the most frequent pathological diagnosis in this cohort, was associated with a higher incidence of CR and a significantly shorter duration to CR.